The Effect of Corporate Governance on Company Financial Performanceat Jakarta Islamic Index - I. Wikartika; F. S. Akbar (Future Science)
The economy in Indonesia is experiencing instability due to intense competition in the era of globalization and the international free market. Alongside this, the implementation of corporate governance in Indonesia is still not able to meet expectations. Thus, it becomes one of the causes of economic instability that has an impact on the company’s financial performance. The Forum for Corporate Governance in Indonesia formulates corporate governance as a corporate governance system that explains the relationship of various participants in determining the direction and performance of the company. Corporate governance is one of the important non-financial components and needs to be considered in an effort to improve company performance. Besides, the development of the capital market in Indonesia could be an economic growth driver by increasing the investment activities. The strong role of the Islamic capital market in the formation of Indonesia’s capital market capitalization indicates the Islamic capital market has a major role in driving Indonesia’s economic growth. This study aims to analyze the influence of the board of commissioners, independent board of directors, the board of directors, and audit committee to the return on equity. The subject of the current research was a company registered in the Jakarta Islamic Index. Research samples were 30 companies registered in the Jakarta Islamic Index for the period June-November 2017. The data analysis techniques used was multiple linear regression. The results showed that the size of the board of commissioners, the board of directors, and the audit committee had no effect on return on equity while the independent board variable had an effect on return on equity.